Adverse and beneficial effects in Chinese hamster lung fibroblast cells following radiofrequency exposure. Issue 4 (10th January 2017) - Sannino, Anna; Zeni, Olga; Romeo, Stefania; Massa, Rita; Scarfi, Maria Rosaria
Abstract : In this study, the effect of radiofrequency (RF) exposure to 1950 MHz, Universal Mobile Telecommunication System signal, was investigated in Chinese hamster lung fibroblast cell line (V79). Genotoxic and cytotoxic effects of 20‐h exposure at specific absorption rate (SAR) values from 0.15 W/kg to 1.25 W/kg were measured by means of cytokinesis‐block micronucleus (MN) assay. Exposure was carried out blinded under strictly controlled conditions of dosimetry and temperature. The effect of RF exposure alone at four SAR values was tested, that is, 0.15, 0.3, 0.6, and 1.25 W/kg. A statistically significant increase in MN frequency was found in cultures exposed to 0.15 and 0.3 W/kg ( P  < 0.05) compared to sham‐exposed ones, in the absence of cytotoxicity. SAR values of 0.6 and 1.25 W/kg did not exert any effect. Moreover, to evaluate the ability of RF to exert protective effects with respect to a chemical mutagen, cell cultures were also pre‐exposed for 20 h at 0.3 or 1.25 W/kg, and then treated with 500 ng/ml of mitomycin‐C (MMC). A significant reduction in the frequency of MN was detected in cultures pre‐exposed to 1.25 W/kg compared to cultures treated with MMC alone ( P  < 0.05), indicating induction of adaptive response. Such a decrease was not induced by pre‐exposure at 0.3 W/kg SAR. Taken together, our results indicated that V79 is a sensitive cell model to evidence either adverse or beneficial effects of RF exposure, depending on experimental conditions applied. Bioelectromagnetics. 38:245–254, 2017. © 2017 Wiley Periodicals, Inc.